Prevalence of Soil-Transmitted Helminth and Schistosoma mansoni Infection and Their Associated Factors among Hiruy Abaregawi Primary School Children, Rural Debre Tabor, North West Ethiopia: A Cross-Sectional Study - Lemma Workineh; Teklehaimanot Kiros; Shewaneh Damtie; Tesfaye Andualem; Bizualem Dessie (Journal of Parasitology Research)
Background. In Ethiopia, 25.3 and 12.3 million school-age children are living in soil-transmitted helminth and schistosomiasis endemic areas, respectively. The school children are at risk for both soil-transmitted helminths and Schistosoma mansoni due to juvenile activities like walking barefoot, playing with dirty objects that might be contaminated with feces, and fetching of unclean water for drinking. There are no data that indicate the status of soil-transmitted helminths and Schistosoma mansoni among children at Hiruy Abaregawi primary school. Therefore, the main objective of this study was to determine the prevalence of soil-transmitted helminth and Schistosoma mansoni infection among Hiruy Abaregawi primary school children. Methods. A cross-sectional study was conducted from March to April, 2019, at Hiruy Abaregawi primary school, Rural Debre Tabor, North West Ethiopia. A total of 340 students were included in the study. Informed written consent was obtained from the children’s parent. Systematic sampling technique was used to select the children. About 2 grams of stool samples was collected and transported to Debre Tabor University Microbiology and Parasitology Teaching Laboratory to conduct the Kato-Katz technique. Data were analyzed using SPSS version 23. Variables with a p value < 0.05 were considered statistically significant. Results. The prevalence of soil-transmitted helminths and Schistosoma mansoni was 51/340 (15%). Among the identified parasites, Ascaris lumbricoides accounts for 28 (8.2%), hookworm 13 (3.8%), Trichuris trichiura 4 (1.2%), and Schistosoma mansoni 6 (1.8%). In this study, 24 (7%) of Ascaris lumbricoides-, 11 (3.2%) of hookworm-, 4 (1.2%) of Trichuris trichiura-, and 5 (1.5%) of Schistosoma mansoni-infected children showed light infections and no heavy infection in both soil-transmitted helminths and Schistosoma mansoni was observed. Finger nail trimming status, hand washing before eating, availability of toilet at home, educational level of students, and sex of students were factors associated with soil-transmitted helminth infection. Conclusion and Recommendations. In this study, the low prevalence of soil-transmitted helminths and Schistosoma mansoni was observed. The combination of regular mass deworming program and health information on risk factors should be strengthened for the prevention and control of soil-transmitted helminth infection.